Uji Reduksi Methylene Blue Terhadap Kontaminasi Bakteri Escherichia coli Pada Susu Sapi Segar di Kelompok Peternak Sapi Perah Desa Cisantana Kabupaten Kuningan: Uji Reduksi Methylene Blue Terhadap Kontaminasi Bakteri Escherichia coli Pada Susu Sapi Segar di Kelompok Peternak Sapi Perah Desa Cisantana Kabupaten Kuningan - Erlangga, Dimas; Nurhayatina, Rina (Jurnal Medika Farmaka, 2025)
The majority of people in Cisantana Village work as livestock farmers, and most of them really enjoy consuming fresh cow's milk. However, most of them are unaware that fresh cow's milk is a food ingredient that contains many bacteria that can cause disease. The purpose of this study was to determine whether there is Escherichia coli contamination in fresh cow's milk from a group of dairy farmers in Cisantana Village and what factors cause this contamination. The method used was colorimetric analysis with the methylene blue reduction test technique. In addition, organoleptic tests, pH, specific gravity, alcohol, and gram staining were also carried out. The samples in this study were fresh cow's milk from 34 farmers. The results showed that of the 34 fresh cow's milk samples, 13 samples tested positive for Escherichia coli contamination. This Escherichia coli contamination was caused by poor barn conditions, equipment, and sanitation.